Cauda equina syndrome caused by retained hemostatic agents. Issue 9 (September 2015) - Bessette, Matthew C.; Mesfin, Addisu
Abstract: We report a patient with cauda equina syndrome secondary to retained Surgicel (Ethicon: Johnson & Johnson Medical, Piscataway, NJ, USA) and Gelfoam (Pfizer, New York, NY, USA). Retained hemostatic agents such as these used in spinal surgery can create space occupying lesions that lead to neurological compromise. There are few reports of neurologic symptoms caused by hemostatic devices used in surgery despite their widespread use. Our patient had routine lumbar microdiscectomy with preexisting motor deficits, and the acute postoperative course was complicated by a decline in neurologic function. The findings at the time of reoperation confirmed compression due to Gelfoam and Surgicel in the spinal canal, and subjective and objective symptoms partially improved after reoperation.